Mastering business analytics and financial modelling: a MOOC course built on gagne's model for optimal online learning / Mohd Shafiz Saharan ... [et al.] - Saharan, Mohd Shafiz; Hassan, Hasroleffendy; Chaleeda, Som Sak; Mohamad Yunus, Fauziah; Mansor, Roseamilda; Ahmad, Nabila (Universiti Teknologi MARA, Kedah, 2023)
The course that is being offered provides a comprehensive introduction to the dynamic and rapidly growing field of business analytics. The course covers the use of data, specifically statistical and quantitative analysis, and the three primary types of analytics - descriptive, predictive, and prescriptive. The use of tools such as Excel and Tableau are emphasized throughout the course to support business analytics. In addition to covering the fundamental concepts of business analytics, the course also delves into the practical application of data mining techniques to support decision making in a business context. Specifically, students will learn how to apply selected data mining techniques to real-world business scenarios. A significant portion of the course is dedicated to financial modelling using Excel. Students will learn how to create comprehensive financial statements, including balance sheets, income statements, and cash flow statements. The use of scenario analysis will also be explored to enable students to evaluate different business decisions and their potential outcomes. To enhance the learning experience, the course utilizes the MOOC UiTM platform, which provides students with a unique and interactive way of learning. This platform is designed to be user-friendly, enabling students to learn and engage with the course material at their own pace. Students are encouraged to actively participate in the delivery of the course, further enhancing their understanding of the concepts covered in the course. In summary, this course provides a solid foundation in the field of business analytics and equips students with the necessary skills to analyse and interpret data in a business context. The practical application of these skills, along with the use of Excel and Tableau, makes this course an excellent choice for anyone interested in pursuing a career in business analytics or data analysis.